2018
DOI: 10.1155/2018/4396018
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Complication Index Predicts Cancer-Specific Survival of Patients with Postoperative Complications after Curative Resection of Gastric Cancer

Abstract: Objective To investigate the prognostic impact of postoperative complications for patients with gastric cancer. Methods Postoperative complications of patients undergoing radical gastrectomy for gastric cancer were reviewed. The severity of complications was graded by the CCI and C-D classification. Results A total of 5327 patients were included in the study. Complications were observed in 767 patients. When the C-D classification system was applied, for patients with grade I–II complications, the length of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Few authors compared the performance of CCI and CDC in other homogeneous surgical procedures, namely, gastrostomies, intestinal resections, cystectomies, liver transplantations, esophagectomies and pancreatectomies [ 20 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Their results are quite consistent with ours in defining CCI as a more precise scale for reporting postoperative morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Few authors compared the performance of CCI and CDC in other homogeneous surgical procedures, namely, gastrostomies, intestinal resections, cystectomies, liver transplantations, esophagectomies and pancreatectomies [ 20 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Their results are quite consistent with ours in defining CCI as a more precise scale for reporting postoperative morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer investigations[ 5 , 6 ] have also observed association between postoperative complications and lower cancer-specific survival. The authors hypothesize that complications could inhibit immune response to spreading tumor cells leading to decreased survival.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the possible influence of these postoperative complications on the long-term survival of patients treated because of gastric cancer[ 5 , 6 ], colo-rectal cancer[ 7 ], colo-rectal liver metastases[ 8 ], or squamous cell esophageal carcinoma[ 9 ]. However, there are no data concerning LT with the exception of papers dealing with graft damage after biliary or ischemic complications[ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This might be related to postoperative weight loss and worsened nutritional status, which could, along with previous comorbidities, lead to performance status decline and worse overall survival. However, it has also been shown that complications impact on cancer‐specific survival, likely as a result of less compliance with adjuvant treatments; such effect was observed both for morbidity as a whole and for severity‐stratified events.…”
Section: Introductionmentioning
confidence: 99%